A micro cell culture method utilizing modified microscope slides for use in fluorescent antibody and enzyme immunoassays - England, J. J. (J Tissue Cult Methods, 1982)
A technique for culturing small quantities of mammalian cells on modified microscope slides is described. The modified microscope slides were Bellco Glass, Inc., toxoplasmosis slides and the cell cultures used were early passage bovine embryonic lung cells and continuous cell lines of porcine and canine origins. The slide cell cultures were either uninfected or infected with selected viruses or the obligate intracellular protozoanEncephalitozoon caniculi for utilization in direct and indirect fluorescent antibody testing or in peroxidase antiperoxidase immunosorbant assays.